A 5-Year Retrospective Review of the Health Supervision Received by Children with Down Syndrome at a South African Regional Hospital. (14th January 2020) - Schoonraad, Leilah; Slogrove, Amy; Engelbrecht, Arnold; Urban, Michael F
Abstract: Introduction: In 2011, the American Academy of Paediatrics (AAP) published revised health supervision guidelines for children with Down syndrome (DS). In the absence of South African guidelines, we described the health supervision received by children with DS at a rural regional hospital in the Western Cape, South Africa compared with the AAP guidelines. Methods: This was a 5-year retrospective description of the implementation of the 2011 AAP guidelines at the DS clinic at Worcester Provincial Hospital (WPH), specifically related to screening for and management of cardiac, thyroid, hearing and haematological disorders. Results: Sixty-two children received care at WPH DS clinic during the study period. Thirty-six (58%) children lived in Worcester while 26 (42%) children were referred from peripheral hospitals. The median age at first clinic visit was 0.5 years [inter-quartile range (IQR) 0.2–1.2], a total of 177 person-years of follow-up with a median duration of 1.8 years (IQR 0.3–4.8). Two deaths occurred during the study period. Forty-nine (79%) children had a screening echocardiogram performed, the median age at first echocardiogram was 0.8 years (IQR 0.2–1.4). Five (14%) children from WPH compared with no children from the peripheral hospitals received the echocardiogram within the first month of life in keeping with AAP guidance ( p = 0.06). Those requiring cardiac surgery were operated on at a median age of 2 years (IQR 0.9–2.3). Compared with the AAP guidelines, within the first month of life 17 (27%) children had a thyroid screen, 20 (32%) children had a full blood count and 7 (11%) children had a hearing assessment. Conclusion: AAP guidelines for health supervision in DS are challenging to achieve within our local health system. The development and advocacy for a South African DS health supervision guideline that can be applied not only in specialist clinics might improve the care of children with DS.